Theoretical Foundations of News Transmission (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this paper, we will examine the transmission of borrowed news using the example of Uzbek and French, analyzing how borrowed vocabulary is adapted and functions in news materials. Uzbek, influenced by both Russian and modern international terms, and French, which actively borrows Anglicisms in the context of global changes, offer an interesting context for study.